Pengaruh Self Efficacy dan Lingkungan Kerja Terhadap Kinerja Pegawai UPTD. Puskesmas Berohol - Desi Windi Ramadani; Dita Yonisa; Rapat Piter Sony Hutauruk; Limega Candrasa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of self-efficacy and work environment on the performance of UPTD employees. Berohol Health Center. The research method used is a quantitative method using SPSS version 25.00. The sample of this study was 34 respondents, namely employees of UPTD. Berohol Health Center, Tebing Tinggi City. The analysis method used in this study was using multiple linear regression analysis and hypothesis testing. The results showed that self-efficacy had a significant effect on the performance of UPTD Berohol Health Center employees, Tebing Tinggi City. The work environment also had a significant effect on the performance of UPTD Berohol Health Center employees, Tebing Tinggi City. Then self-efficacy and work environment simultaneously influenced employee performance at UPTD Berohol Health Center, Tebing Tinggi City.